The Nuances of Brand Personality: A Corpus-assisted Linguistic Analysis of Web-based Communications of Fashion Brands - Camiciottoli, Belinda Crawford (HERMES - Journal of Language and Communication in Business, 2018)
The ability to establish a particular brand personality (i.e. a set of human personality traits that consumers associate with a brand) is a key component of fashion brand management and communication. A given fashion brand may use language that communicates different personality traits (e.g. glamourous, exciting, youthful, exotic) as a way to define its own personality and distinguish itself from other fashion brands. Based on a corpus consisting of company-produced texts collected from the websites and Facebook pages of over 100 fashion brands, this study aimed to determine which traits of brand personality emerge, which are the most frequent, and which nuances of meaning can be identified within them. This was accomplished by means of text analysis software that identifies statistically significant semantic domains to which conceptually-related lexical items are assigned. The analysis revealed 14 key semantic domains that were linked to various brand personality traits. Among the most prominent were Judgement of appearance: Positive, Time: New and young, Relationship: Intimacy and sex, and Unexpected, highlighting not only the traditional importance attributed to attractiveness, but also to sensuality and non-conventionality as desirable traits of fashion brand personality. Other distinctive traits that emerged as significant involved exclusivity (encoding the value of elitism) and iconicity (emphasizing high stature and uniqueness). The study offers insights into how fashion brands utilize web-based communications to convey brand personality. It also offers a useful methodology that fashion companies can adapt to ensure that they are effectively communicating the intended brand personality.